Environmental Management in Local Wisdom Perspective of Karampuang People, Sinjai District, South Sulawesi - Syarif, Erman (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2017)
Indigenous peoples of Karampuang are very obedient to customs, beliefs, cosmology, and knowledge in environmental management. This study aims to determine the local wisdom of indigenous people KarampuangSinjai regency in South Sulawesi in environmental management. Type of qualitative research with case study approach. Technique of data collection is done by observation, interview, documentation and literature review. Data analysis techniques used are data collection, data reduction, Data Presentation, and Withdrawal Conclusion. Research results show that indigenous peoples of Karampuang manage the environment derived from local wisdom in the form of knowledge, myths and messages of ancestors that contains prohibitions, invitations, and sanctions in environmental management. Local wisdom is important to be conserved in order to maintain balance and environmental sustainability.